ZIRCON SHRIMP U-PB DATING, C AND O ISOTOPES FOR IMPURE MARBLES FROM THE JIAOBEI TERRANE IN THE SULU OROGEN: IMPLICATION FOR TECTONIC AFFINITY - Tang J.; Zheng Y.F.; Wu Y.B.; Gong B. (My University, 2006)
Middle Neoproterozoic carbonates are found in the western part of Shandong Pennisula (i.e., the Jiaobei terrane) that is located in the northwestern part of the Sulu orogen in east-central China. For the first time, a successful SHRIMP U-Pb dating, coupled with CL imaging, was conducted on two samples of impure marble from the Fenzishan Group in this tectonic unit. The results yield consistent ages of 786 ± 67 and 240 ± 44 Ma for igneous and metamorphic zircons, respectively. Positive δ13C values as high as +5.6‰ are measured for both pure and impure marbles, consistent not only with the worldwide Neoproterozoic limestones in connection with the Sturtian ice-age, but also with the marbles associated with UHP metamorphic eclogites in the Dabie orogen. O isotope fractionation between calcite and garnet from one sample gave a temperature of 680 °C, pointing to upper amphibolite-facies metamorphic conditions. These results indicate that protolith of the marbles is a kind of limestone that was synchronously deposited with volcaniclastic rocks in the mid-Neoproterozoic rift basin of continental margin. Like the UHP metamorphic rocks in the Dabie-Sulu orogenic belt, both mid-Neoproterozoic magmatism and Triassic metamorphism are recorded in the impure marbles. Therefore, protolith of the impure marbles corresponds to the sedimentary limestone of rift basin developed during the mid-Neoproterozoic breakup of supercontinent Rodinia, but it was the sedimentary cover along the northern margin of the South China Block prior to its Triassic subduction. The occurrence of the mid-Neoproterozoic limestone with the Triassic metamorphism in the southern margin of the North China Block thus indicates tectonic overthrust by a crustal detachment between the sedimentary cover and the Precambrian basement during the continent subduction. As a result, the marbles in affinity to the South China Block were northward thrusted over the basement of the North China Block. © 2005 Elsevier B.V. All rights reserved.
Keywords: CONTINENT SUBDUCTION; CRUSTAL DETACHMENT; NEOPROTEROZOIC LIMESTONE; TECTONIC OVERTHRUST; TRIASSIC METAMORPHISM; Triassic; Neoproterozoic; Mesozoic::Triassic; Мезозой::Триасовая; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская